Distance Learning: Education or Economics? - Simmons, Jack R. (International journal of value-based management, 2001)
Sir John Daniel, Vice Chancellor of the Open University in England, pronounced that American universities are in a crisis of access, flexibility and cost. His solution is that American Universities and Colleges should employ educational technologies that allow students to earn college degrees without visiting the college campus (distance learning). The argument is that distance learning is a cost-effective way of providing more students with access to higher education. Sir John's argument illustrates a crisis in neither access, flexibility, nor cost. On further inspection, distance learning degree programs appear to be a strategy for reducing the cost of higher education by replacing professors with computers and part-time teachers. This strategy offers limited educational benefits for the student and may present a financial danger to smaller colleges and universities, if they succumb to the pressure to develop distance, learning degree programs.